Does it matter that medical graduates don't get jobs as doctors? No. Issue 7651 (1st May 2008) - Maynard, Alan
Abstract : Last year's shortfall in training places looks set to be repeated. Graham Winyard (doi: 10.1136/bmj.39555.457060.AD ) believes this is a betrayal of students' expectations, but Alan Maynard thinks it is inevitable if patients are to get the best care